Management of cleft palate in middle schooler: A case report - Joshi, KR; Das, G; Shrestha, A; Khanal, LR; Guragain, M (Journal of Nepalese Prosthodontic Society, 2023)
A cleft lip and/or palate is a congenitally persistent fissure in the upper lip, alveolus, hard palate, or soft palate that can contribute to hearing loss, speech impediment, feeding issues, dental malocclusion, and nasal deformity. The oronasal communication reduces the capacity to produce the essential negative pressure for sucking and causes nasal regurgitation of food and may even lead to choking. The feeding plate seals the fissure and restores the wall separating the nasal cavity from the oral cavity.